The WIC Infant and Toddler Feeding Practices Study-2 (WIC ITFPS-2) Through Age 5: What We've Learned, What Questions Remain, and How You Can Use This Longitudinal Dataset. (7th June 2021) - Paolicelli, Courtney; Borger, Christine; DeMatteis, Jill; Gollapudi, Bibi; Machado, Janice; Reat, Amanda; Ritchie, Lorrene; Sun, Brenda; Whaley, Shannon; Zimmerman, Thea Palmer
Abstract: Objectives: By the end of the session, attendees will be able to: (1) Articulate the methodology of and notable findings from the USDA WIC Infant and Toddler Feeding Practices Study-2 (WIC ITFPS-2); and (2) Summarize the major domains of data available through age 5 in the WIC ITFPS-2 public use dataset. Methods: The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) is the premier public health nutrition program for low-income, nutritionally at-risk pregnant and post-partum women, infants, and children up to age five. To better understand how WIC participation is associated with the health and nutrition outcomes of young children, USDA funded the WIC Infant and Toddler Feeding Practices Study-2 (ITFPS-2) in 2011. WIC ITFPS-2 is a national, longitudinal study of 3775 mother-child dyads who enrolled in WIC either during the mother's pregnancy or shortly after the child was born. The study interviews participants every 2 to 6 months through the child's fifth birthday, with two additional follow-ups at ages 6 and 9 years. The study captures information on children's health and nutrition status, including 24 hour dietary recall data; mothers' feeding practices and beliefs; household food security; and WIC participation patterns. Data are weighted to produce national estimates. As of June 2021, data through children's fifth birthday (i.e., all years during which children were categorically eligible for WIC) are publicly available. Results: Using descriptive, univariate, and multivariate techniques, analyses across the first 6 study reports have demonstrated positive associations between WIC and diet outcomes among young children. After controlling for other factors, longer WIC participation was associated with higher Health Eating Index-2015 scores at various time points, with lower daily energy intake, and with meeting the Dietary Guidelines recommendation to limit added sugar. Conclusions: Across children's first five years of life, WIC participation has been associated with improved dietary intake and better diet quality, among other positive outcomes. The WIC ITFPS-2 dataset is publicly available and should be leveraged by researchers to further explore the health and nutrition status of low-income children during the early years of life. Funding Sources: WIC ITFPS-2 is funded by USDA contract number AG-3198-B-11–0020 with Westat.